A Feasibility study on a locally manufactured Private Automatic Branch Exchange (PABX) - Godinez, Raquel Rosario Y.; Sugay, Paul Philip T.; Veron Cruz, Rolan Paul K. (Diliman, Quezon City College of Engineering, 1993)
The microelectronics industry, in particular the telecommunications industry is an industry which holds a potential for expansion in the country. This study endeavored to present the advantages and limitations of locally manufacturing an indigenously designed telephone switching system. The feasibility study encompasses an analysis of the present market and the possibilities of marketing the product, the technical aspect involved in the setting up of a manufacturing plant and the intricacies of actual manufacture, the financing required and the benefits that financiers will derive from their investment into the business venture, and the effects that this project will have on the society and the economy. The requirements for telephone switching systems, specifically KTS and PABX systems are met by only two sources: 1) foreign companies such as Siemens, Alcatel, and Goldstar; and 2) PLDT, who is also supplied by the same companies. Of the current market, 60% is PLDT's share while the rest is composed of other the companies. The scheme employed by PLDT is that each system is rented out on a monthly basis. The other companies, on the other hand have outright sales or they also have the option of having their systems rented out. Evaluation of PLDT's records revealed that there is a larger demand for the smaller capacity models, namely the KTS and miniBX systems. The capacities of these systems range from 1x2 to 6x16 requirements. The ASTI-GC8 telephone switching system can easily handle the size requirements. PLDT catered to those whose requirements fell into the larger sized systems. The targeted market was the KTS and miniBX market because of system capacity. Derived from the information from PLDT was the identification of the location of the market and the different key locations with respect to the Metro Manila market. Four major locations were identified, namely Makati, Malate, Intramuros and Mandaluyong. These areas were used in the preparation of the marketing strategy employed for this venture. Lastly, the records provided the necessary historical information to project the future demand for these switching systems. A small percentage of the market was targeted and from this necessary forecasts for the desired 5-year program were made. The technicalities involved in the manufacture of the system showed that the processes involved are simple. Labor requirements were derived from the time figures from another microelectronics manufacturer together with the use of the MODAPTS system currently employed overseas. The result of the time study shows that the amount of time required to produce one system is 75 man-hours. As indicated in the market study, the requirements for the planned 5-year period were derived. From these figures together with the necessary time to assemble on product the plant capacity and subsequent schedules were derived. The necessary list of raw materials utilized for the system came from the ASTI engineers, the designers of the system. Most of the components can be sourced from local suppliers within the vicinity. Not all the parts of the system are produced by the company; the casing of each system is subcontracted amounting to a cheaper alternative. Lastly, the information from ASTI provided the basis for the necessary estimates of project costs. Also, the costs involved in the transfer of the technology to the manufacturer. The financial study was done to determine the profitability of the venture. This involved the manipulation of cash flows so as to minimize losses and make the project profitable. To achieve this, the different terms of financing were researched and he most attractive one provided 70% of the project's cost at 16% interest rate per annum payable in five years. Using this and the estimated cost of the first three years, it was computed that the owners of the company would provide P2,250,000 and borrow P1,500,000 on the first year to cover initial expenses and operating costs, and borrow another P1,500,000 on the second year to cover materials and operating costs. The interest of these two loans were to be paid at the end of the year it was borrowed and the payment for the principal of both loans commenced on the third year up to the fifth year. Despite the negative income for the first year, the second year earnings reaped a positive return. The company's overall performance was rated using three financial ratios: 1) Debt-to-Net worth-Ratio, this ratio is used to determine the capacity to meet long term obligations using equities 2) Debt Ratio, while this makes use of the total assets, 3) return on assets, this shows the earning power of the project. Manpower requirements were arrived at in the Technical study. The resulting organizational structure is simple for only the three main functions of management were considered. There is no general manager for the company which is established as a partnership, there is only an interconnection of the different functions and departments. Each of these departments is given freedom to decide on localized problems. The project is not for the purpose of producing income for the company but it also has a direct effect on society and economy. Jobs are created employing the community directly and indirectly, providing more income to the individual and to their families. This increase in income allows an increase in the taxes due to the government. These taxes in turn may be used for education and infrastructure that directly affect society. Another dimension is the vision of an industrialized Philippines, Philippines 2000. ASTI, together with other science and technology based institutions want to transfer technology to the local designer, inventor, manufacturer and entrepreneur.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Telecommunication systems; Intercommunication systems; Participatory monitoring and evaluation (Project management)